2016
DOI: 10.4048/jbc.2016.19.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Portrait of the Normal Human Breast Tissue and Its Influence on Breast Carcinogenesis

Abstract: Normal human breast tissue consists of epithelial and nonepithelial cells with different molecular profiles and differentiation grades. This molecular heterogeneity is known to yield abnormal clones that may contribute to the development of breast carcinomas. Stem cells that are found in developing and mature breast tissue are either positive or negative for cytokeratin 19 depending on their subtype. These cells are able to generate carcinogenesis along with mature cells. However, scientific data remains contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 124 publications
2
11
0
5
Order By: Relevance
“…In HER2-transformed cells, TGFβ further stimulated HER2 signaling to promote malignancy and induced resistance to anti-HER2 therapy. The observations in the present study showed changes in cellular responsiveness, and confirmed the previously reported promotion of transformation by EGF and TGFβ1, the stimulatory effect of 17β-estradiol, and the inhibitory effects of Iressa and tamoxifen (3)(4)(5)(6)(7)(8)43,44). The observations also confirmed that long-term exposure may contribute to the development of resistance to Iressa in 17β-estradiol-exposed cells, and to SB431542 in EGF-and/or 17β-estradiol-exposed cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In HER2-transformed cells, TGFβ further stimulated HER2 signaling to promote malignancy and induced resistance to anti-HER2 therapy. The observations in the present study showed changes in cellular responsiveness, and confirmed the previously reported promotion of transformation by EGF and TGFβ1, the stimulatory effect of 17β-estradiol, and the inhibitory effects of Iressa and tamoxifen (3)(4)(5)(6)(7)(8)43,44). The observations also confirmed that long-term exposure may contribute to the development of resistance to Iressa in 17β-estradiol-exposed cells, and to SB431542 in EGF-and/or 17β-estradiol-exposed cells.…”
Section: Discussionsupporting
confidence: 92%
“…EGF and 17β-estradiol are known stimulators of cell proliferation (3)(4)(5)(6)(7)(8)(9). The present study observed that prolonged exposure resulted in faster proliferation of McF7 cells, and this higher rate of proliferation was maintained even upon removal of EGF and 17β-estradiol from the medium (Fig.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Unlike MGB, MVD count is not restricted to the malignantly transformed breast tissue, its use being extended to a wide range of human benign and malignant conditions. MGB is one of the markers of the normal and malignantly transformed breast tissue where it can be detected in two main forms with different molecular masses [1,2]. When investigating the human MGB gene, in 1998, Watson et al [3] have concluded that it is not ver y well conserved phylogenetically and it presents a series of architectural similarities with uteroglobin genes and rat prostatein subunits.…”
mentioning
confidence: 99%
“…Using fluorescent in situ hybridization, the MGB gene has been localized on chromosome 11q13 which is usually amplified in breast cancer [3]. Increased MGB protein expression in breast cancer patients is associated with a favorable prognosis although its implications and functions are not yet fully understood [1,4]. MGB-A, one of the members of the secretoglobin superfamily, is expressed in most breast cancer cells and is currently being studied as a potential therapeutic target in immune therapies [5].…”
mentioning
confidence: 99%